1976
DOI: 10.1071/wr9760011
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Reproduction and Age Structure of the Fox, Vulpes vulpes L., in New South Wales

Abstract: A total of 838 foxes were collected throughout New South Wales from 1969 to 1974. In every month of the year there were some males producing sperm but there was a major peak of activity during June, July and August. The major period of female reproductive activity commenced in July and reached a peak in August. There were indications that some females ovulated during February and March although no pregnancies were recorded outside June-October. At least 30 % of vixens suffered preplacentation loss of ova or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…The litter size, a parameter that is affected by habitat quality, found in the steppe habitat following rabbit haemorrhagic disease is one of the lowest reported anywhere (Kolb and Hewson 1980, Harris and Smith 1987, Goszczyñski 1989. The most similar results are those given for New South Wales (Ryan 1976), and two Mediterranean areas in Spain (Ruiz-Olmo et al 1990, Zapata et al 1998). Conversely, the litter size of the vegas foxes is similar to those reported in most European studies (eg Lloyd 1980 and references therein).…”
Section: Reproductionsupporting
confidence: 73%
“…The litter size, a parameter that is affected by habitat quality, found in the steppe habitat following rabbit haemorrhagic disease is one of the lowest reported anywhere (Kolb and Hewson 1980, Harris and Smith 1987, Goszczyñski 1989. The most similar results are those given for New South Wales (Ryan 1976), and two Mediterranean areas in Spain (Ruiz-Olmo et al 1990, Zapata et al 1998). Conversely, the litter size of the vegas foxes is similar to those reported in most European studies (eg Lloyd 1980 and references therein).…”
Section: Reproductionsupporting
confidence: 73%
“…Foxes were easily observed and counted by spotlight surveys before the study and it was found that they typically did not take flight from spotlight beams or vehicles when >50 m from the observer. The red fox is seasonally monoestrous and vixens will produce a single litter each year (Ryan 1976). The timing of this study between October and November 2002 was chosen to coincide with the fox breeding season immediately before the emergence of cubs from breeding dens in Melbourne Marks and Bloomfield 1999) and before the dispersal of yearling animals (Robinson and Marks 2001).…”
Section: Study Populationmentioning
confidence: 99%
“…The red fox is annually monoestrous, and the vixen will produce a single litter each year after a gestation period of 52-53 days (Lloyd and Englund 1973;Ryan 1976;Coman 1983;McIlroy et al 2001). The birth of cubs occurs within an established natal den and cubs are dependent upon the shelter that dens provide for a number of weeks thereafter (Robertson et al 2000).…”
Section: Introductionmentioning
confidence: 99%